Analisis Fenomena Separasi Energi Ranque âHilsch Vortex Tube Menggunakan Kaji Eksperimental dan Simulasi Numerik - , RADI SURADI KARTANEGARA, Ir. Samsul Kamal, MSc, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to look at the influence of the inlet air pressure variations and variations in the number of nozzles used in Ranque-Hilsch vortex tube (shortened to RHTV), and then finally get the relationship between the decrease of temperature at the end of cold oulet section (ïTc) and cooling efficiency (ï¨v) toward in changes of the cold mass fractions (ïc). To obtain of RHTV results performances, two steps process was carried out, ie experimentally and numeric simulation In experiment at laboratorium, The RHTV which used has a 10 mm diameter and 100 mm long. Inlet air pressure used is varied between 2, 3, 4 and 5 bar and amount of nozzles mounted on RHTV varies ie 2, 3 and 4 nozzle (where the total of cross-sectional area of nozzle used created equal). Whereas in the process of numerical simulations, which use CFD software Numeca Fine 7.3 with K-Îµ turbulence model, from numerical simulation results used to compare experimental results RHTV using 3 and 4 nozzles at a pressure of 5 bar and on cold fraction around 48.1% which is then analyzed to see the nature of the distribution of air in the RHTV Experimental results on cold fraction between 20% to 90% and at various pressures, RHTV with 3 nozzles generally has lower performance than RHTV with 2 and 4 nozzles, while RHTV the nozzle 4 has better performance than RHTV the nozzle 2. On the pressure of 5 bars, RHTV with 2 or 4 nozzles have the same relative performance In general, the influence of variation inlet pressure which used on relationship of ïTc and ï¨v toward an increase ïc on each RHTV will increase when the inlet pressure increased as well.. The results of numerical simulation shows the temperature distribution in axial directions of RHTV increased towards the end hot sectiont, but for section of cold end the temperatur decline occurs. The results also show the phenomenon of the compression process in RHTV both radially in the tube cross section and axially toward hot end section, while toward of cold end section the expansion process occurs. Another resulsts shows, that the temperature and pressure distribution on RHTV with 4 nozzles are lower than RHTV with 3 nozzles, this agrees with the experimental results.